High Cancer Susceptibility Candidate 8 Expression Is Associated With Poor Prognosis of Pancreatic Adenocarcinoma: Validated Analysis Based on Four Cancer Databases - Wang, Yingyi; Yang, Yuemei; Wang, Yanfeng; Li, Xiaoou; Xiao, Yu; Wang, Wenze (Frontiers in Cell and Developmental Biology, 2020)
Objective: To explore the association between the expression of an lncRNA, CASC8 (cancer susceptibility candidate 8) and pancreatic adenocarcinoma (PAAD). Materials and methods: starBase database was used to perform differential expression, survival, as well as ceRNA networkand H19/miR-671 correlation analyses for CASC8 in 178 PAAD samples. Using the cBioPortal database website, we analyzed the alteration in CASC8 expression and its correlation with the overall survival in PAAD. GO and KEGG enrichment analysis were also performed using the circlncRNAnet database. Analysis of CASC8 polymorphisms was performed using the UCSC Xena database. Finally, the expression of CASC8 in Chinese PAAD tissues was validated by qPCR. Results: The expression of CASC8 was observed to be high in 178 PAAD samples (foldchange=8.71, P=0.0014,FDR=0.04), and was related with poor prognosis, but not in pNET. CASC8 amplification was noted in 6% of the PAAD patients, however, the gene amplification did not affect the expression of CASC8 but was involved with the overall survival time of PAAD patients. Network analysis indicated that H19 is the ceRNA pair of CASC8, and CASC8 competitively binds to miR671 and might participate in the process of EMT. The correlation analysis showed that CASC8 was significantly negatively correlated with SMAD7. The analysis of CASC8 polymorphism showed that high copy number segment of CASC8 is associated with low survival. Validation using PAAD tissues from Chinese patients was consistent with the in-silico findings. Conclusion: CASC8 is specifically expressed at high level in PAAD and associated with poor prognosis, which might be through its interaction with H19, miR-671 and SMAD7. These results indicate that CASC8 could serve as a novel marker for predicting the prognosis and as a potential target for the therapy of PAAD.